2007
DOI: 10.1080/02699050701553205
|View full text |Cite
|
Sign up to set email alerts
|

Treatment to improve self-awareness in persons with acquired brain injury

Abstract: The self-awareness intervention significantly but selectively improved self-awareness during IADL task performance as well as functional performance. The need for a larger study with more treatment sessions is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
90
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(97 citation statements)
references
References 42 publications
6
90
1
Order By: Relevance
“…25,38,41 In 2 studies, the effects were not statistically tested, but the authors reported a positive treatment effect on awareness (PND 36%-81%). 40,43 However, in these studies, the positive treatment effects appeared to be task specific.…”
Section: High-quality Studiesmentioning
confidence: 93%
See 4 more Smart Citations
“…25,38,41 In 2 studies, the effects were not statistically tested, but the authors reported a positive treatment effect on awareness (PND 36%-81%). 40,43 However, in these studies, the positive treatment effects appeared to be task specific.…”
Section: High-quality Studiesmentioning
confidence: 93%
“…In 2 studies, therapists recommended patients for awareness treatment based on clinical judgment of evidence of impaired self-awareness. 38,43 In one study, patients were included if they underestimated their memory deficits (incongruence between predicted memory performance and actual performance), 40 and in another study, patients had a SADI score greater than 0 (mean SADI score at baseline was 5). 25 Furthermore, studies reported high SRSI scores (range: 6-10), 42,44 high SADI scores (8), 39 and a large difference score on the AQ (range: [22][23][24][25][26][27][28][29][30] 42 at baseline.…”
Section: High-quality Studiesmentioning
confidence: 99%
See 3 more Smart Citations